Research progress of dihydromyricetin in the treatment of diabetes mellitus - Wang, Ziyuan; Cao, Zhuoran; Yue, Zhiying; Yang, Zhengfeng (Frontiers in Endocrinology, 2023)
Diabetic Mellitus (DM), a chronic metabolic disorder disease characterized by hyperglycemia, is mainly caused by the absolute or relative deficiency of insulin secretion or decreased insulin sensitivity in target tissue cells. Dihydromyricetin (DMY) is a flavonoid compound of dihydroflavonol that widely exists in Ampelopsis grossedentata. This review aims to summarize the research progress of DMY in the treatment of DM. A detailed summary of related signaling induced by DMY are discussed. Increasing evidence implicates that DMY display hypoglycemic effects in DM via improving glucose and lipid metabolism, attenuating inflammatory responses, and reducing oxidative stress, with the signal transduction pathways underlying the regulation of AMPK or mTOR/autophagy, and relevant downstream cascades, including PGC-1α/SIRT3, MEK/ERK, and PI3K/Akt signal pathways. Hence, the mechanisms underlying the therapeutic implications of DMY in DM are still obscure.In this review, following with a brief introduction of the absorption, metabolism, distribution, and excretion characteristics of DMY, we summarized the current pharmacological developments of DMY as well as possible molecular mechanisms in the treatment of DM, aiming to push the understanding about the protective role of DMY as well as its preclinical assessment of novel application.